STRATEGI PENGEMBANGAN PERTANIAN ORGANIK SAYURAN DI KELURAHAN KAKASKASEN DUA KECAMATAN TOMOHON UTARA KOTA TOMOHON - Juwita Walewangko; Juliana R. Mandei; Lyndon R.J. Pangemanan; Ellen G. Tangkere (Universitas Sam Ratulangi, 2015)
ABSTRACTJuwita Walewangko. Organic Vegetables Farming Development Strategy in Kakaskasen Two village, District of North Tomohon in Tomohon (under Guidance Juliana Mandei as Chairman, Lyndon Pangemananan and Ellen G.Tangkere as Members).The purpose of this study is to identify the internal conditions: strengths, weaknesses, and external: opportunities, threats in the development of organic farming of vegetables in Kakaskasen Two village of North Tomohon district in Tomohon city and to formulate the development strategies of organic farming of vegetables in the village.Data collection was conducted over three months, since november 2014 until the month of February 2015. The data collection method is a survey method. The data obtained are primary data and secondary data. The primary data obtained through Focus Group Discussion (FGD) and interviews directly to the department of Agriculture, Head of Kakaskasen Two village, farmer groups, farmers and consumers. Next the secondary data obtained through Badan Penyuluhan Pertanian Perikanan dan Kehutanan (BP3K) of North Tomohon in Tomohon. The sample were 30 respondents of organic vegetable farmers in which consist of 5 people tomato farmers, 15 farmers cauliflower and cabbage 10 farmers. SWOT analysis were used in this research to analyse the data.The results of this study indicate that a force for the development of organic farming vegetable farmers have experienced and mastered the technology, has a cooperation agreement with the Department of Agriculture, Head Kakaskasen two, and BP3K, organic production facilities are available and that the weakness is the future land conversion requires considerable time that is 2-3 years old, organic productivity is low, there is no labeling of organic products so the price is the same as the inorganic. Organic agriculture has the opportunity to be developed in the Village Kakaskasen two is the support of the government, increasing the public keasadaran to consume organic vegetables but face a threat that is the competition with other local farmers and reduced consumer confidence in the market because it is generally not 100 percent organic. Agricultural development strategy of organic vegetables in the Village Kakaskasen two are improving the ability and skills possessed by farmers, organic vegetables and quality assurance in cooperation with the Department of agriculture, and the labeling BP3K colored according to the levels of organic vegetables, to socialize constantly, and expand organic vegetable farming to benefit from access to capital as well as increased public awareness to consume organic products. Keywords: Organic Vegetables, Factor Internal, External Factors and Strategies.